Living on the Edge Innovative Research on Leaving Care and Transitions to Adulthood - Keller, Samuel; Oterholm, inger; Paulsen, Veronika; van Breda, Adrian D. (Research in Social Work series, 2023)
EPDF and EPUB available Open Access under CC-BY licence. Young people transitioning out of care towards independence, work and adulthood are on the edge of these phases of life. Considering previously neglected groups of care leavers such as unaccompanied migrants, street youth, those leaving residential care, young parents and those with a disability, this book presents cutting-edge research from emerging global scholars. The collection addresses the precarity experienced by many care leavers, who often lack the social capital and resources to transition into stable education, employment and family life. Including the voices of care leavers throughout, it makes research relevant to practitioners and policymakers aiming to enable, rather than label, vulnerable groups.